Dickens's Style - Tyler, Daniel (Cambridge : Cambridge University Press, 2013)
Charles Dickens, generally regarded as the greatest novelist of the Victorian age, was known as 'The Inimitable', not least for his distinctive style of writing. This collection of twelve essays addresses the essential but often overlooked subject of Dickens's style, with each essay discussing a particular feature of his writing. All the essays consider Dickens's style conceptually, and they read it closely, demonstrating the ways it works on particular occasions. They show that style is not simply an aesthetic quality isolated from the deepest meanings of Dickens's fiction, but that it is inextricably involved with all kinds of historical, political and ideological concerns. Written in a lively and accessible manner by leading Dickens scholars, the collection ranges across all Dickens's writing, including the novels, journalism and letters.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).